El impacto del deterioro medioambiental del Mar Menor en los precios de Airbnb; The environmental degradation impact in Mar Menor on Airbnb prices - María del Mar Fernández Ferrero; Ricardo Teruel Gutiérrez; Mariluz Maté Sánchez De Val (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2022)
– In 2008, the company Airbnb started its activity becoming the most representative tourism accommodation company from the sharing economy. Nowadays, it has more than 6.500.000 registered listings around the world. Previous literature examines hedonic models where Airbnb's prices are explained in function of accommodation characteristics. In this context, studies about the environmental degradation effects on Airbnb listing prices are practically nonexistent. Citiciens are concerned about the marine pollution problems in the tourist area of Mar Menor (Murcia). The advances in micro-territorial open databases (as the information from the Senitel 3 satellite provided by the European Spatial Agency) allow improving the hedonic models accuracy and determining the economic impact of marine water pollution on Airbnb prices located in this coastal area. This is the objective of our study. The results show a significant impact of high levels of marine water pollution in Mar Menor reducing Airbnb listing prices in this zone. Therefore, managers in the tourism sector have incentives to adopt measures to reduce marine pollution in order to reduce the environmental degradation in this lagoon.
Keywords: C2; D16; L83; 330; hedonic models; Airbnb listings; marine pollution; open databases